Gross Stocks Estimated from Past Installations - Schiff, Eric (The Review of Economics and Statistics, 1958)
foreign supply curve AC and demand curve JM are unaffected by devaluation, while, upon devaluation to the extent indicated by AB(=JK), the home supply curve in terms of foreign currency shifts downward from its initial position (not drawn), passing through J, to KM, and the home demand curve in terms of foreign currency shifts downward from its initial position (not drawn), passing through A, to BC. Thus M is the new equilibrium position in the export market, and C that in the